EFFECTIVENESS OF PCR POOL TESTING FOR SCREENING OF COVID-19 INFECTION IN PAKISTAN - Ahmad, Nasir; Azra; Muhammad, Hafsah; Khan, Ishaq N; Siraj, Sami; Ahmad, Sajjad; Zakria, Muhammad; Asif Ali; Yasar Mehmood Yousafzai (Journal of Ayub Medical College Abbottabad, 2022)
Background: We tested the utility of mini-pool PCR testing for the rational use of PCR consumables in screening for CoViD-19. Methods: After pilot experiments, 3-samples pool size was selected. One-step RT-PCR was performed. The samples in the mini-pool having COVID gene amplification were tested individually. Results: 1548 samples tested in 516 mini-pools resulted 396 mini-pools as negative and 120 as positive. Upon individual testing, 110 samples tested positive and 9 were inconclusive. 876 PCR reactions were performed to test 1548 samples, saving 43% PCR reagents. Centres with low prevalence resulted in most saving on reagents (50%), while centres with high prevalence resulted in more test reactions. Testing of individual samples resulted in delays in reporting. Conclusion: Pooling can increase lab capacity, however, pooling delays results and cause degradation of samples.